Shaping climate resilient pathways : integrative approach for monitoring and evaluation of climate resilience and climate change adaptation - Wilden, Daniela; Justus Liebig University Giessen (My University, 2022)
Climate resilience and climate adaptation have started to play an essential role in research, international and national politics, as well as at local level. Also in Germany, the impacts of climate change is undeniable. Cities are increasingly facing the challenge of adapting to the (anticipated) impacts and enhancing the climate resilience of the urban system and societies. Urban areas are considered to be highly complex and interconnected adaptive social-ecological systems embedded in the acceleration of climate and societal change. Due to this multi-layered complexity, it is challenging to assess the success of resilience-building measures, while, evaluation is very important to accelerate learning processes, reduce maladaptation and design climate resilient pathways. The paper aims to develop an integrating, cross-scale (spatial and temporal) monitoring and evaluation approach for climate resilience and adaptation to provide a scientific basis for practical application. For this purpose, a mix-method approach is pursued at the three different levels – intervention, system and actor level. The spatial focus of the study is on Ger-many. The results reveal that each scale has specific benefits and limitations with regard to monitoring and assessing climate resilience and adaptation measures. Particularly important is raising awareness and the behavioural change of the actors in the adaptation projects and this underlines the central role of actors in the transformation process. Based on empirically validated indicators for the respective levels, monitoring is possible at the short, medium and long-term levels as well as at the level of individual actors up to the regional system. Drawing on these results, an integrative approach for monitoring and assessing climate resilience and adaptation is derived. The critical discussion of the research results highlights both the need for further research and opportunities for further development of the integrative approach and the learning and transformation process.
Entwicklung klimaresilienter Pfade: Integrativer Ansatz für Monitoring und Evaluation von Klimaresilienz und Klimaanpassung
Keywords: Klimaanpassung; Climate adaptation; Climate resilience; Cities; Monitoring and Evaluation; Klimaresilienz; ddc:300; ddc:910